Remote Auditing, AI, Litigation Risk, and Due Professional Care Moderating Audit Quality - Noor Laeliya, Aida; Anis Charir (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2026)
This research investigates the impact of remote auditing, artificial intelligence (AI), and litigation risk on audit quality, examining the moderating role of due professional care. Employing a quantitative approach with data collected from auditors in Indonesian Public Accounting Firms, the research addresses the evolving audit landscape. The findings confirm that both remote auditing and AI significantly enhance audit quality by improving accuracy, efficiency, and real-time evidence evaluation. Conversely, litigation risk shows no significant relationship with audit quality, suggesting that external legal pressure is not yet a dominant behavioral driver for Indonesian auditors. The moderation analysis offers a key insight: due professional care strengthens the positive effect of remote auditing but fails to enhance the effects of AI or litigation risk. This research underscores the critical need for auditors to possess digital competence and exercise professional judgment to fully leverage digital technologies and optimize audit performance in the digital era.